2013
DOI: 10.1179/2047058412y.0000000072
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the gum dichromate process in pictorialist photographs: A literature review and technical study

Abstract: In the late 1800s, pictorialist photographers favored a diversity of photographic techniques, including the gum dichromate process. Sometimes superimposed over other photographic images such as platinum and silver prints, the gum dichromate process utilizes a light-sensitive mixture of gum arabic, pigment, and a potassium dichromate solution hand-applied onto a sheet of paper and exposed to light while in direct contact with a negative. The definitive identification of this process has proven to be a challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The chemical composition of all four plates, one of which was attributed by the authors to a particular pewter smith was conrmed by XRF. The 'gum dichromate' process was used by late 19 th century pictorialist photographers and Vila et al 256 prepared test samples which were analysed by the XRF technique in an attempt to develop a method to identify this process. They reported that the presence of Cr might have more complex sources so that a more discriminatory approach was required for the identication of gum dichromate photographs.…”
Section: Archaeological and Cultural Heritagementioning
confidence: 99%
“…The chemical composition of all four plates, one of which was attributed by the authors to a particular pewter smith was conrmed by XRF. The 'gum dichromate' process was used by late 19 th century pictorialist photographers and Vila et al 256 prepared test samples which were analysed by the XRF technique in an attempt to develop a method to identify this process. They reported that the presence of Cr might have more complex sources so that a more discriminatory approach was required for the identication of gum dichromate photographs.…”
Section: Archaeological and Cultural Heritagementioning
confidence: 99%
“…This information was used to prepare gum dichromate samples in order to establish the XRF protocols to characterize the elemental composition of photographs bearing this medium. The results obtained showed that it is possible to state that a dichromate colloid technique was used if, in addition to the presence of pigments and gum, the amounts of Cr detected by XRF correlate with the density of the image, with relatively larger amounts in the darker areas [11], also commonly referred to in the literature as high image density areas. A mixture of gelatin and chrome alum, KCr(SO 4 ) 2 ·12H 2 O, was recommended in some historic sources to size the paper substrates in gum prints to limit the penetration of the colloid, and therefore to improve the quality of the image, and was also used with a similar purpose in other photographic techniques such as carbon-transfer or platinum, among others.…”
Section: Introductionmentioning
confidence: 94%
“…A review of these recipes can be found in [11]. Arches MBM® paper was used as a substrate due to its similarities to the papers used during the period.…”
Section: Gum Dichromate Print Samplesmentioning
confidence: 99%
See 1 more Smart Citation